Certolizumab pegol in combination with dose-optimised methotrexate in DMARD-naïve patients with early, active rheumatoid arthritis with poor prognostic factors: 1-year results from C-EARLY, a randomised, double-blind, placebo-controlled phase III study. Issue 1 (10th May 2016) - Emery, P; Bingham, C O; Burmester, G R; Bykerk, V P; Furst, D E; Mariette, X; van der Heijde, D; van Vollenhoven, R; Arendt, C; Mountian, I; Purcaru, O; Tatla, D; et al.
Abstract : Objectives: To assess the efficacy and safety of certolizumab pegol (CZP)+dose-optimised methotrexate (MTX) versus placebo (PBO)+dose-optimised MTX in inducing and sustaining clinical remission in DMARD-naïve patients with moderate-to-severe, active, progressive rheumatoid arthritis (RA), with poor prognostic factors over 52 weeks. Methods: DMARD-naïve patients with ≤1 year of active RA were randomised (3:1) in a double-blind manner to CZP (400 mg Weeks 0, 2, 4, then 200 mg Q2W to Week 52)+MTX or PBO+MTX (the mean optimised-MTX dose=21 and 22 mg/week, respectively). Sustained remission (sREM) and sustained low disease activity (sLDA; DAS28(ESR)<2.6 and DAS28(ESR)≤3.2, respectively, at both Weeks 40 and 52) were the primary and secondary endpoints. Results: Patients were randomised to CZP+MTX (n=660) and PBO+MTX (n=219). At Week 52, significantly more patients assigned to CZP+MTX compared with PBO+MTX achieved sREM (28.9% vs 15.0%, p<0.001) and sLDA (43.8% vs 28.6%, p<0.001). Inhibition of radiographic progression and improvements in physical functioning were significantly greater for CZP+MTX versus PBO+MTX (van der Heijde modified total Sharp score (mTSS) mean absolute change from baseline (CFB): 0.2 vs 1.8, p<0.001, rate of mTSS non-progressors: 70.3% vs 49.7%, p<0.001; least squares (LS) mean CFB in Health Assessment Questionnaire-Disability Index (HAQ-DI): −1.00 vs −0.82, p<0.001). Incidence of adverse events (AEs) and serious AEs was similar between treatment groups. Infection was the most frequent AE, with higher incidence for CZP+MTX (71.8/100 patient-years (PY)) versus PBO+MTX (52.7/100 PY); the rate of serious infection was similar between CZP+MTX (3.3/100 PY) and PBO+MTX (3.7/100 PY). Conclusions: CZP+dose-optimised MTX treatment of DMARD-naïve early RA resulted in significantly more patients achieving sREM and sLDA, improved physical function and inhibited structural damage compared with PBO+dose-optimised MTX. Trial registration number: NCT01519791.